2017
DOI: 10.1007/s11631-017-0237-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of non-carbonate mineral weathering as a soil formation mechanism within a karst weathering profile in the SPECTRA Critical Zone Observatory, Guizhou Province, China

Abstract: Soil degradation, including rocky desertification, of the karst regions in China is severe. Karst landscapes are especially sensitive to soil degradation as carbonate rocks are nutrient-poor and easily eroded. Understanding the balance between soil formation and soil erosion is critical for long-term soil sustainability, yet little is known about the initial soil forming processes on karst terrain. Herein we examine the initial weathering processes of several types of carbonate bedrock containing varying amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
(10 reference statements)
1
10
0
2
Order By: Relevance
“…Tipper et al, 2006;Pogge von Strandmann et al, 2008). This is consistent with simple isotope mass balance considerations that dictate that Mg isotopes are not fractionated during complete dissolution of minerals, such as expected for weathering of magnesite or brucite (Mumpton and Thompson, 1966;Moore et al, 2017). Accordingly, measurable suggest that some of the above alteration products can form at near-ambient temperatures (De Obeso et al, 2020;Streit et al, 2012).…”
Section: Mg Isotopic Constraints On Weatheringsupporting
confidence: 78%
“…Tipper et al, 2006;Pogge von Strandmann et al, 2008). This is consistent with simple isotope mass balance considerations that dictate that Mg isotopes are not fractionated during complete dissolution of minerals, such as expected for weathering of magnesite or brucite (Mumpton and Thompson, 1966;Moore et al, 2017). Accordingly, measurable suggest that some of the above alteration products can form at near-ambient temperatures (De Obeso et al, 2020;Streit et al, 2012).…”
Section: Mg Isotopic Constraints On Weatheringsupporting
confidence: 78%
“…They correlated these contents with mineral and elemental contents in the overlying soils to conclude that the soils were formed from the bedrock impurities and not via deposition of transported material. Non-carbonate mineral contents can vary even within a single outcrop as observed by Moore et al (2017) who found adjacent beds in Puding County, Guizhou, with 4, 25, and 33% non-carbonate mineral contents. Based on the abundances of non-carbonate (largely silicate) mineral impurities in the bedrock of the karst…”
Section: Bedrock Weathering and Soil Formationmentioning
confidence: 82%
“…The substantial rainfall of the sub-tropical monsoonal climate of southwest China promotes rapid carbonation (although higher temperatures will slow the rate as carbon dioxide (CO2) is less soluble at higher temperatures), and subsequently, only minimal amounts of undissolved mineral particles are available for soil formation in karstic systems of the region. Therefore, in the absence of aeolian deposition, soil formation in karst areas depends on "impurities" within the bedrock, predominantly silicate minerals, which provide both a structural matrix and additional elements, many of which are essential macroand micro-nutrients (Wang et al 1999;Moore et al 2017). Wang et al (1999) examined bedrock from five sites across Guizhou and Hunan provinces and found 11.6 -38.8% noncarbonate residual mineral content in the limestones and 0.6 -4.0% residual content in the dolostones.…”
Section: Bedrock Weathering and Soil Formationmentioning
confidence: 99%
“…They are characterized by exposed carbonate rocks that weather rapidly and are highly susceptible to environmental change and natural erosion. In China, the karst landscape in the southwest region has experienced rapid and intensive alterations to land use and associated ecosystem degradation over the last 50 years (Chen et al, 2018; Li et al, 2018; Moore et al, 2017). The intensification of agriculture since the late twentieth century has led to a rapid deterioration of the soil, reflected in reduced crop production and the rapid loss of soil (Green et al, 2019).…”
Section: Introductionmentioning
confidence: 99%